EFFORTS TO IMPROVE COGNITIVE LEARNING ACTIVITIES AND RESULTS IN FIQIH LESSONS THROUGH THE TOURNAMENT TEAM GAME MODEL WITH QUARTET MEDIA (Quashi Experiment at Madrasah Ibtidaiyah in Padalarang) - Dede Ramdani; Bambang Samsul Arifin; Dindin Jamaluddin; Arif Maryadi (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2020)
This research stems from the low learning activities of students in joining fiqh learning and the low cognitive learning outcomes of students in fiqh subjects. The purpose of this study was to determine the increase in activity and cognitive learning outcomes of students in the class V Fiqh subject. The quantitative approach used in this study, with the Quashi experiment method nonequivalent control group (comparison group / pretest posttest) design. Data collection tools used in this study were observation and tests. Based on the results of research conducted in class V Islamic of elementary school  Al-Adzkar and Sabilil Huda in Padalarang sub-district, it shows that the application of the team game tournament model with quartet card media can increase the learning activities of students with an average increase of 76%. Likewise, the cognitive learning outcomes of students experienced a significant increase, at MI Al-Adzkar the average learning outcomes increased to 75.8 from 33.8, while at MI Sabilil Huda the average rose to 71.00 from 38, 00. AbstrakPenelitan ini bermula dari rendahnya aktivitas belajar peserta didik dalam mengikuti pembelajaran fikih serta rendahnya hasil belajar kognitif peserta didik pada mata pelajaran fikih. Tujuan dari penelitian ini untuk mengetahui peningkatan aktivitas dan hasil belajar kognitif peserta didik pada mata pelajaran fikih kelas V. pendekatan kuantitatif yang digunakan pada penelitian ini, dengan metode Quashi eksperiment nonequivalent control grup (comparison group/pretest posttest) design. Alat pengumpulan data yang digunakan dalam penelitian ini adalah observasi dan tes. Berdasarkan pada hasil penelitian yang dilakukan pada kelas V Madrasah Ibtidaiyah Al-Adzkar dan Madrasah Ibtidaiyah Sabilil Huda yang berada di kecamatan Padalarang menunjukan bahwa penerapan model team game tournament dengan media kartu quatet dapat meningkatkan aktivitas belajar peserta didik dengan rata-rata peningkatan 76%. Begitu juga dengan hasil belajar kognitif peserta didik mengalami peningkatan yang cukup signitfikan, pada MI Al-Adzkar rata-rata hasil belajar naik menjadi 75,8 dari 33,8, sedangkan pada MI Sabilil Huda rata-ratanya naik menjadi 71,00 dari 38,00.